A note on exponentially bounded stopping times of certain one-sample sequential rank order tests - Z. Govindarajulu (International Journal of Mathematics and Mathematical Sciences)
A simple proof of the exponential boundedness of the stopping time of the one-sample sequential probability ratio tests (SPRT's) is obtained.